Early serum creatinine changes and outcomes in patients admitted for acute heart failure: the cardio-renal syndrome revisited. Issue 5 (August 2017) - Núñez, Julio; Garcia, Sergio; Núñez, Eduardo; Bonanad, Clara; Bodí, Vicent; Miñana, Gema; Santas, Enrique; Escribano, David; Bayes-Genis, Antonio; Pascual-Figal, Domingo; Chorro, Francisco J; Sanchis, Juan
Background: The changes in renal function that occurred in patients with acute decompensated heart failure (ADHF) are prevalent, and have multifactorial etiology and dissimilar prognosis. To what extent the prognostic role of such changes may vary according to the presence of renal insufficiency at admission is not clear. Accordingly, we sought to determine whether early creatinine changes (ΔCr) (admission to 48–72 hours) had an effect on 1-year mortality relative to the presence of renal insufficiency at admission. Methods: We included 705 consecutive patients admitted with the diagnosis of ADHF. Admission renal insufficiency was defined as serum creatinine ≥1.4mg/dl (A-RIcr ) or estimated glomerular filtration rate <60ml/min/1.73m 2 (A-RIGFR ). Appropriate survival regression techniques were used. Results: The mean age was 72.9±11.4 years and 51.2% were males. Patients with admission renal insufficiency (24.7% and 42.8% for A-RIcr and A-RIGFR, respectively) had higher prevalence of extreme values in ΔCr in either direction (increasing/decreasing). At 1-year follow-up, 114 (16.2%) deaths were registered. The multivariable analysis showed a significant interaction between admission renal insufficiency and ΔCr ( p =0.004 and p =0.019 for A-RIcr and A-RIGFR, respectively). In the presence of renal insufficiency, the continuum of ΔCr followed a positive and almost linear relationship with mortality risk. Conversely, in patients without renal insufficiency, those changes adopted a 'J-shape' trajectory with increased mortality at both ends of the curve distribution. Conclusions: In patients with ADHF the effect of ΔCr on 1-year mortality varied according to its magnitude and the presence of admission renal insufficiency. There was a graded-association with mortality when renal insufficiency was present on admission.